The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/gps.1700
|View full text |Cite
|
Sign up to set email alerts
|

Treating late‐life depression with interpersonal psychotherapy in the primary care sector

Abstract: IPT is an effective treatment for late-life depression whose greater use by primary care physicians should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…In both study groups, physicians were informed by letter if patients reported any suicidal ideation and immediately when patients were identified as being at high risk for suicide according to prespecified guidelines. Other sources detail the PROSPECT treatment algorithm and implementation, including the role of the care manager (29), strategy for pharmacotherapy (28), management of suicidal ideation (30,31), and types and proportions of treatment received over time by patients in practices randomly assigned to the intervention or to usual care (14,32).…”
Section: Articlementioning
confidence: 99%
“…In both study groups, physicians were informed by letter if patients reported any suicidal ideation and immediately when patients were identified as being at high risk for suicide according to prespecified guidelines. Other sources detail the PROSPECT treatment algorithm and implementation, including the role of the care manager (29), strategy for pharmacotherapy (28), management of suicidal ideation (30,31), and types and proportions of treatment received over time by patients in practices randomly assigned to the intervention or to usual care (14,32).…”
Section: Articlementioning
confidence: 99%
“…The patients in the intervention group ceased to have identifiable suicidal ideation more rapidly, and their depression diminished more readily and more completely compared with the treatment-as-usual group, although the differences among the groups with respect to remission rates were not significantly different at the 1-year mark [34]. The proportion of patients receiving any form of psychotherapy was greater in the intervention group, and IPT use was noted to increase in the intervention practices over time [35]. .…”
Section: Ongoing Research Using Ipt With Older Adultsmentioning
confidence: 96%
“…The care manager also could provide brief evidence-based psychotherapy such as problem-solving therapy, [39][40][41][42] if counselors are not available to deliver extended but time-limited therapies, such as cognitive behavioral therapy [43][44][45][46] or interpersonal therapy. [47][48][49] Step 8. Specify activities of other depression care team members Typically, PCPs are expected to be responsible for detecting and diagnosing depression, prescribing antidepressants, and referring patients to the collaborative care program.…”
Section: Step 3 Specify Target Patients and Identification Proceduresmentioning
confidence: 99%